2009
DOI: 10.2337/db09-1233
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GPR40 in Pancreatic  -Cells Augments Glucose Stimulated Insulin Secretion and Improves Glucose Tolerance in Normal and Diabetic Mice

Abstract: OBJECTIVE-GPR40 is a G protein-coupled receptor regulating free fatty acid-induced insulin secretion. We generated transgenic mice overexpressing the hGPR40 gene under control of the mouse insulin II promoter and used them to examine the role of GPR40 in the regulation of insulin secretion and glucose homeostasis.RESEARCH DESIGN AND METHODS-Normal (C57BL/6J) and diabetic (KK) mice overexpressing the hGPR40 gene under control of the insulin II promoter were generated, and their glucose metabolism and islet func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…In contrast, impairment of β‐cell function was observed in FFAR1 overexpressing transgenic mice, indicating that FFAR1 expression is regulated by the insulin promoter factor 1/pancreatic and duodenal homeobox 1 promoter 24. Also, a line of mice has been developed that overexpresses FFAR1 under the control of an insulin promoter, and their phenotypic characterization showed that FFAR1 could partly mediate GSIS 31. These results suggest that FFAR1 might contribute to the mechanism related to obesity and metabolic disorders.…”
Section: Free Fatty Acid Receptor 1 (Gpr40)mentioning
confidence: 99%
“…In contrast, impairment of β‐cell function was observed in FFAR1 overexpressing transgenic mice, indicating that FFAR1 expression is regulated by the insulin promoter factor 1/pancreatic and duodenal homeobox 1 promoter 24. Also, a line of mice has been developed that overexpresses FFAR1 under the control of an insulin promoter, and their phenotypic characterization showed that FFAR1 could partly mediate GSIS 31. These results suggest that FFAR1 might contribute to the mechanism related to obesity and metabolic disorders.…”
Section: Free Fatty Acid Receptor 1 (Gpr40)mentioning
confidence: 99%
“…G protein-coupled receptor 40 [GPR40, also known as free fatty acid receptor 1 (FFAR1)] [8] is highly expressed in pancreatic β-cells and activated by long-chain free fatty acids (FFAs) [9,10]. FFAs are an important energy source, and they also act as signalling molecules for modulating insulin secretion [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…FFAs are an important energy source, and they also act as signalling molecules for modulating insulin secretion [11][12][13]. Most of the insulinotropic effects of FFAs appear to be mediated through GPR40, since GPR40specific small interfering RNA and antisense oligonucleotides inhibit fatty acid-induced insulin secretion [9][10][11][12][13][14]. It has been postulated that FFAs interact with GPR40 with a resultant increase in cytosolic Ca 2+ via phospholipase C and L-type Ca 2+ channels [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both of these claims have been countered. [7][8][9][10][11] It has been shown recently that human islets cultured long term in the presence of a GPR40 antagonist (ANT203, Fig. 1) showed a 40 number of beneficial effects, including inhibition of the detrimental effects of palmitate on glucose stimulated insulin secretion and insulin content, 12 although perhaps contrary results have also been described.…”
mentioning
confidence: 99%